Dynamic Characteristics and Mechanism of the Saturated Compacted Loess under Freeze-Thaw Cycles. (8th October 2021) - Wang, Qian; Liu, Fuqiang; Zhong, Xiumei; Gao, Zhongnan; Liang, Shouyun; Liang, Yuxin
Abstract : To study the dynamic characteristics and mechanism of saturated loess after freeze-thaw cycles, a series of laboratory tests including freeze-thaw cycle tests, dynamic triaxial tests, and scanning electron microscope tests of the saturated remolded loess was conducted. The characteristics of the dynamic parameters of the saturated loess after different freeze-thaw cycles were discussed. The characteristics of the microstructure parameters changes were analyzed. The evolution process and mechanism of the microstructure of the remolded loess under freeze-thaw cycles were proposed. The results show that after different freeze-thaw cycles, the dynamic stress-dynamic strain curves of the saturated remolded loess conform to the hyperbolic model; however, the freeze-thaw cycle has a significant effect on the model parameter b . With the increase of freeze-thaw cycles, the dynamic shear modulus of saturated remolded loess first decreases and then increases, while the damping ratio is opposite. When saturated remolded loess experiences freeze-thaw cycles greater than four, its dynamic stability is better than that of saturated soil without freeze-thaw cycles. The dynamic stability reaches its peak after seven freeze-thaw cycles and is equivalent to that of saturated soil without freeze-thaw cycles after forty cycles. Combined with the results of the quantitative analysis of microstructure images, with the increase of the freeze-thaw cycles, the number of large and medium particles in the soil reduces, and the number of micros and small particles increases. The particle size tends to be uniform. The apparent porosity increases rapidly and then decreases sharply and tends to be stable after 4 freeze-thaw cycles. The pore and particle fractal dimensions continue to decrease. The probability of entropy increases first and then decreases. It is illustrated that the saturated loess has mainly experienced three steps under freeze-thaw cycles: (1) fracture and expansion of original skeleton cementation, (2) damage, crushing and aggregation of the particle, and (3) compaction and reorganization of soil structure. Besides, the saturation condition significantly accelerates the evolution process of the internal structure of the soil under freeze-thaw cycles. These lead to the strengthening effect of soil dynamic stiffness under long-term freeze-thaw cycles.